Potential of Cycling to Reduce Emissions in Road Transport. Executive Summary. - Ahrens, Gerd-Axel; Becker, Udo; Böhmer, Thomas; Richter, Falk; Wittwer, Rico (My University, 2013)
The aim of the project was to obtain reliable estimates of the potential of cycling transport regarding environmental relief. The task was to study scenarios for integrated promotion of cycling transport and sustainable transport development with respect to mode choice, destination, vehicle kilometres and emissions. With the help of a statistical model developed for the project, different parameters were analysed and varied in order to estimate changes in driven kilometres and environmental impacts. By varying the model parameters structural changes and hypothetical assumptions in the sense of if-then combinations were able to be integrated into the modelled variations (sensitivity analyses). Using the resulting system knowledge scenarios of measures were subsequently recursively conceptualised at a general level and the breadth of impact was estimated. The outcome reveals that shifting short car trips up to five kilometres only effects a small change in CO2 emissions of one to three percent since the share of these trips in driven kilometres is small. If cycling were to be used for destinations (further away) perceived by the public as having good cycling accessibility then the potential for reductions increases considerably to between six and 11 percent of total CO2 emissions in workday passenger transport. If along with mere shifts, strategies for avoiding or reducing traffic are integrated into the model then driven kilometres and CO2 emissions are reduced by 19 to 38 percent and 13 to 27 percent respectively. The results allow conclusions to be drawn as to the potential for cycling transport to reduce emissions and provide guidance on fitting this potential into holistic, sustainable strategies. Thus the contribution of modal shift away from the personal vehicle as well as of avoiding long car trips then becomes clear. On the whole it was determined that there is potential for cycling in Germany to reduce greenhouse gas emissions. (UBA)
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Stadtverkehr; Verkehrsmittelwahl; Fahrradbenutzung; Nachhaltige Mobilität; Potenzialanalyse; Klimaschutz; Emissionsminderung